Analytical modeling of tool-workpiece contact rate and experimental study in ultrasonic vibration-assisted milling of Ti–6Al–4V. (July 2018) - Ni, Chenbing; Zhu, Lida; Liu, Changfu; Yang, Zhichao
Highlights: An analytical model for calculating tool-workpiece contact rate (TWCR) in ultrasonic vibration assisted milling (UVAM) was proposed. The oscillation characteristics, amplitude reduction and FFT spectrum of force signal in UVAM was demonstrated. An on-line monitoring system is used to monitor processing stability and record vibration characteristics. A series of experiments were conducted to study the effect of machining parameters on the machining performance of TC4 and UVAM technical advantages were verified. Relatively short, thin and uniform chips are produced and uniform ultrasonic vibration texture appears on chips morphology in UVAM. Abstract: Ultrasonic machining (UM) method is characterized by separate-type cutting that the tool and workpiece will undergo numerous times of separation and contact in machining process. Based on intermittent machining mechanism in UM, this paper presented an analytical model for calculating the tool-workpiece contact rate (TWCR) in ultrasonic vibration assisted milling (UVAM). The non-periodic distribution of contact and separation points between the tool and workpiece, which is caused by continuous change of critical velocity, greatly increases the complexity of intermittent machining in UVAM. According to the proposed TWCR theoretical model in UVAM, the nominal cutting speed, vibration frequency, vibration amplitude and rotation angle are four key parameters affecting TWCR. Since machining parameters are closely related to the TWCR, so a series of ordinary milling and UVAM experiments were conducted to study the effect of machining parameters on machining performance of Ti–6Al–4V. Experimental results showed that UVAM method had obvious technical advantages in reducing cutting force, improving finished surface quality, suppressing burrs and optimizing chip formation. In this paper, the advantages of ultrasonic machining mechanism were explained from the perspective of TWCR. The oscillation characteristics, amplitude reduction characteristics and FFT spectrum characteristics of original cutting force signal in UVAM were analyzed. Moreover, the effect of machining parameters on surface roughness and topography in UVAM was investigated. And the influence mechanism of ultrasonic vibration on burr suppression and chip formation was also introduced and studied. Experiment results verified the superior of UVAM method compared to ordinary milling under the same cutting condition. Graphical abstract: